Politeness Strategies Used by Students to Teachers in Their Communication at Pesantren Salaf Al Quran Sholahul Huda Al-Mujahidin Malang - Zakaria, Bahrudin Nur Aziz; Anggarini, Ida Fitri; Agustina, Debi Olivia; Billa, Delfia Ayu Salsa; Amanda, Dhea Sherly; Al Maula, Faijatul (ELITE JOURNAL, 2026)
This study on politeness strategies used by students to their teacher in their communication at Pondok Pesantren Salaf Al-Quran Sholahul Huda Al-Mujahidin Malang was conducted to examine the types of politeness strategies employed by both students and teachers in their daily communication. Four teachers or ustadz of Pesantren Salaf Al-Quran Sholahul Huda Al-Mujahidin and 13 students or santri were chosen as the participants. Further more, a case study qualitative approach by doing observation and interview was employed as the method of the study. To figure out the phenomenon, Brown and Levinson’s (1987) theory of politeness strategies was applied in analyzing the data. From the analysis, it was figured out that all types of politeness strategies were realized in teachers’ utterances. In contrast, only three politeness strategies were performed bt students. It was identified that the three social factors of power, social distance and ranking of imposition triggered the students and teachers to perform such strategies. However, another influential factor that was found to encourage the participants to employ those strategies was that Pesantren Salaf Al-Quran Sholahul Huda Al-Mujahidin’s culture that encompasses several values which are based upon the Islamic values declared in Al Quran and Al Hadith. Keywords: Pesantren, culture, politeness strategies, santri, ustadz